Decision making in darkness: an analysis of initial decision making prerequisites in public projects in Iceland - Andri Már Reynisson 1985- (2012)
Large public projects in Iceland suffer from frequent cost overruns. No indications of increased accuracy in estimations over time and with increased experience are visible. These estimations are amongst the foundations or prerequisites of initial decisions of undertaking large public projects, using public funds. Prerequisites for decisions should be reflected in the outcome of the decision, along with other environmental factors that are beyond the control of management. Two of the prerequisites for initial decision making and selection of public projects in Iceland are the knowledge of decision makers in Parliamentary committees and the guidance for decisions that is provided in guidelines for decision making and project selection. In this dissertation, the consistency of these decision making and selection prerequisites to best practices is benchmarked. Best practices are divided into four fields of practices from project management and decision analysis. The findings indicate significant gaps between best practices and the analysed prerequisites of decision making and selection of large public projects. Among further findings presented, the presence of cognitive bias was confirmed amongst decision makers and the majority of Members of Parliament consider it important to issue a benchmark of recognized and defined methods that committee members could use to assist them in decision making about important issues. Issuing of formal benchmarks in consistency with best practices for initial decision making and selection of public projects in Iceland is suggested as a long term solution. For short term improvements, implementation of methods from the Green Book, the UK guideline for public project decision making and project selection, is suggested. Stór opinber verkefni á Íslandi fara oft fram úr kostnaðaráætlunum. Engin sjáanleg merki eru um aukna nákvæmni í áætlunum með aukinni reynslu. Þessar áætlanir eru meðal forsendna þess að ráðist er í opinber verkefni, fyrir skattfé. Forsendur ákvarðanatöku ættu að ...